A remotely accessible plant-based culinary intervention for Latina/o/x adults at risk for diabetes: lessons learned - Koh, Linda M.; Iradukunda, Favorite; Martínez, Airín D.; Caetano Schulz, Keila C.; Bielitz, Irene; Walker, Rae K. (Frontiers in Nutrition, 2024)
1) Introduction: Little research has examined how community-engaged and -participatory dietary interventions adapted to remotely-accessible settings during the COVID-19 pandemic;(2) Objectives: To identify lessons learned in design, implementation, and evaluation of a remotelyaccessible, community-based, nurse-led approach of a culturally-tailored whole food plant-based culinary intervention for Latina/o/x adults to reduce type 2 diabetes risk, delivered during a pandemic; (3) Methods: A mixed methods quasi-experimental design consisting of a pre-post evaluation comprised of questionnaires, culinary classes, biometrics, and focus groups; (4) Lessons Learned: Community partnerships are essential for successful recruitment/retention. To optimally deliver a remotely-accessible intervention, community leadership and study volunteers should be included in every decision (e.g., timeframes, goals). Recommendations include managing recruitment and supply chain disruption of intervention supplies; (5) Conclusions: Future research should focus on increasing accessibility and engagement in minoritized and/or underserved communities, supply chain including quality assurance and delivery of services/goods, study design for sustainable, remotely-accessible interventions, and health promotion.